Limited ecological population connectivity suggests low demands on self-recruitment in a tropical inshore marine fish (Eleutheronema tetradactylum: Polynemidae) - Horne, J.; Momigliano, P.; Welch, D.; Newman, Stephen; Van Herwerden, L. (Wiley-Blackwell Publishing, 2011)
The diversity of geographic scales at which marine organisms display genetic variation mirrors the biophysical and ecological complexity of dispersal by pelagic larvae. Yet little is known about the effect of larval ecology on genetic population patterns, partly because detailed data of larval ecology do not yet exist for most taxa. One species for which this data is available is Eleutheronema tetradactylum, a tropical Indo-West Pacific shorefish. Here, we use a partial sequence mitochondrial cytochrome oxidase subunit 1 (COI) marker and five microsatellite loci to survey the genetic structure of E. tetradactylum across northern Australia. Structure was found throughout the range and isolation by distance was strong, explaining approximately 87 and 64% of the genetic variation in microsatellites and mtDNA, respectively. Populations separated by as little as 15 km also showed significant genetic structure, implying that local populations are mainly insular and self-seeding on an ecological time frame. Because the larvae of E. tetradactylum have lower swimming performance and poor orientation compared with other tropical fishes, even modest larval abilities may permit self-recruitment rather than passive dispersal. © 2011 Blackwell Publishing Ltd.